Randomized phase II study of TX followed by XELOX versus the reverse sequence for chemo-naive patients with metastatic gastric cancer - Zhao, Xiao-Yin; Liu, Xin; Li, Wen-Hua; Qiu, Li-Xin; Huang, Ming-Zhu; Wang, Chen-Chen; Chen, Zhi-Yu; Zhang, Wen; Feng, Wan-Jing; Guo, Wei-Jian; Zhu, Xiaodong (Frontiers in Oncology, 2022)
Background Docetaxel, platinum and fluorouracil are the three most important drugs in the treatment of MGC, but few studies have explored whether docetaxel-based doublet regimen is as effective as platinum-based. This study was to compare clinical outcomes of the docetaxel capecitabine combination and the oxaliplatin capecitabine combination as first-line therapy in MGC patients. Methods In this phase II trial, MGC patients were randomly assigned and treated with either TX (capecitabine 1000 mg/m2/twice daily/1-14 days and docetaxel 60-75 mg/m2 on the 1st day) or XELOX (capecitabine the same dose with TX and oxaliplatin 130 mg/m2 on the 1st day) as first-line therapy. After progression, patients were crossover to the other group as second-line treatment. Results Total 134 MGC patients were randomized (69 in TX, 65 in XELOX). There was no significant difference between the PFS of the two groups (TX vs XELOX, 4.6 months vs 5.1 months, p=0.359), and the SFS (9.3 months vs 7.5 months, p=0.705), OS (13.1 months vs 9.6 months, p=0.261), and ORR (46.4% vs 46.2%) were also similar. Among patients with ascites, the TX group had significantly longer PFS and OS than the XELOX group. A total of 85 patients (48 in TX, 37 in XELOX) received second-line treatment, with overall survival of second-line chemotherapy (OS2) of 8.0 m and 5.3 m (p=0.046), respectively. Grade 3 to 4 treatment-related adverse events of first line treatment occurred more in TX group (60.6% vs 55.4%). Conclusion: TX regimen is an alternative choice of first-line treatment for MGC patients.